PENGARUH REVIEW ONLINE, KUALITAS LAYANAN, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Novita, Angela; Soeparto, Alexander Wahyudi Henky (Universitas Ciputra Surabaya, 2023)
This study aims to determine the effect of Online Reviews, Service Quality, and Consumer Trust on Purchase Decisions on the Shopee platform. This type of research is quantitative research where the population in this study is all people who have used the Shopee application. The sample in this study was 85 respondents using the online questionnaire data collection method, namely the Google form. The sampling technique of this study uses Non-Probability with Purposive Sampling Techniques. In this study, the data were processed using multiple linear regression analysis techniques. The results of this study indicate that 1) online reviews have a significant effect on purchasing decisions, 2) service quality has a significant effect on purchasing decisions, 3) consumer trust has a significant effect on purchasing decisions.